Jaco the galactic patrolman - Toriyama, Akira, 1955- (Viz Media, 2015)
Retired scientist Omori lives alone on a deserted island while continuing his research into time-travel. His quiet life is interrupted when galactic patrolman Jaco crash-lands and decided to move in with him. This agent from space claims to be elite, but sometimes it can be a little hard to believe. Can Jaco get along with the old man long enough to save the earth from a dangerous threat?